Formation Of Individual Education Methodology For Future Music Teachers - Qayumov J. S. (Euro Asian Journal Publishing, 2024)
the article examines the skills of future music teachers in the formation of individual educational methods
Keywords: folk music heritage; national idea; ideology; education